Behavioral and Developmental Changes in Brown Trout After Exposure to the Antidepressant Venlafaxine - Ziegler, Michael; Banet, Michel; Bauer, Rebecca; Köhler, Heinz-R.; Stepinski, Sabine; Tisler, Selina; Huhn, Carolin; Zwiener, Christian; Triebskorn, Rita (Frontiers in Environmental Science, 2021)
During the last decades, depression has been diagnosed in increasing numbers, accompanied by rising prescription rates of antidepressants. Concomitantly, these pharmaceuticals are frequently detected in surface waters. Serotonin and noradrenalin reuptake inhibitors such as venlafaxine form the second largest group of antidepressants worldwide, and venlafaxine is the second most prescribed antidepressant in Germany. As drug targets are evolutionary highly conserved, venlafaxine can potentially change not only behavior and related physiological processes in humans but also in non-target species, especially aquatic organisms. In order to test this hypothesis for fish, we exposed brown trout larvae and juveniles to venlafaxine at concentrations ranging from 1 to 1,000 μg/L. Larvae were exposed for 5 months from the eyed ova stage until 8 weeks post yolk-sac consumption at 7 and 11 °C. Juveniles were exposed for 4 weeks at 7 °C. Mortality, weight, length, behavior during exposure and behavior in a stressful environment were recorded in both experiments. For larvae, additionally, hatching rate and heart rate were analyzed. In juvenile fish, tissue cortisol levels were determined. Our results clearly showed, that brown trout, irrespective of their life stage, change their behavior when being exposed to venlafaxine: During exposure, venlafaxine at 7 °C caused larvae to sojourn in the upper part of the aquaria for a longer time, with a lowest observed effect concentration of 100 μg/L. In a stressful environment with limited space, fish exposed to ≥10 μg/L venlafaxine were less active than controls. Furthermore, venlafaxine reduced the growth of larvae (length at ≥10 μg/L, weight at 1 mg/L) and their survival after 5 months (at 1 mg/L). Hatching rate and heart rate of larvae as well as tissue cortisol concentration of juveniles were not affected by venlafaxine treatment.